Internet and quality standards of learning in Natural Sciences in a school in Arenillas - Maldonado-Ramirez, Raymon L. (2020)
This research work was carried out with the objective of demonstrating how the use of the internet affects the quality standards of learning in the area of ​​Natural Sciences of the students of the 5th year, Arenillas High School, Province of Oro-Ecuador. It is a descriptive level investigation and assumes the correlational design. The population and sample consisted of 92 members of the mentioned institution. Two instruments were applied: the survey technique and the instrument the structured questionnaire to measure the first variable; The other measuring instrument was an evaluation of the students to measure the quality standards of the area of ​​natural sciences. To measure the correlation that exists between these two variables, the Pearson ratio coefficient was used, which shows that there is a correlation of 0.857, which shows that there is a significant incidence between the use of the internet and the quality standards of Learning in the studied population. Then, it is stated with a level of confidence of 95% that significant incidence between both variables, therefore, the use of the internet improves student learning.